Genotypic variability and trait associations for cold stress tolerance in cultivated chickpea (Cicer arietinum L.) during the reproductive stage - Deeksha Padhiar; Sarbjeet Kaur; Swarup K. Parida; Uday C. Jha; Kamal Dev Shama; Pagadala Venkat Vara Prasad; Kadambot H. M. Siddique; Harsh Nayyar (PLoS ONE, 2026)
Chickpea ( Cicer arietinum L.), a major winter legume in northern South Asia and Australia, frequently encounters low temperatures (0–15 °C) during reproduction, causing substantial yield losses. The present study involved screening two independent sets of 100 genotypes over consecutive winters to identify sources of reproductive-stage cold tolerance and to elucidate the underlying mechanisms. Following outdoor establishment, plants were exposed to controlled cold stress (15/7 °C day/night) during flowering and pod development (15 d) in walk-in growth chambers. Ten representative cold-tolerant (CT) and ten cold-sensitive (CS) genotypes were selected each year based on integrated performance across yield, physiological, biochemical, and reproductive traits for a detailed mechanistic analysis. Cold-sensitive genotypes exhibited severe dysfunction, characterized by high electrolyte leakage (50−59% above CT) and malondialdehyde (39−51% above CT), indicating membrane damage. Reduced chlorophyll content (21−23%), photosystem II efficiency (23−29%), and stomatal conductance (40−43%) impaired photosynthesis. Inadequate cryoprotectants (reduced by 25−58%) and antioxidants (reduced by 38−55%) caused oxidative damage. Reproductive collapse followed, with pollen viability and germination declining by 24−46%, stigma receptivity and ovule viability decreasing by 41−68%, and seed yields falling by 85−95%. Cold-tolerant genotypes-maintained homeostasis through integrated protection in terms of superior membrane stability, enhanced compatible solutes, and elevated antioxidant activities, which sustained photosynthesis and reproductive success, achieving better yields under cold stress. Principal component analysis revealed cold tolerance as an integrated system (PC1:72.6–81.3% variance), clearly separating the CT from the CS genotypes. Membrane stability, photosynthetic efficiency, and pollen viability emerged as diagnostic traits (r = 0.85–0.91 with yield, p < 0.001; heritability 70−99%). Tolerance operated independently of maturity (R² = 0.10–0.18), enabling donor identification across maturity classes. Twenty cold-tolerant genotypes were identified, spanning the early, medium, and late maturity groups, respectively. These findings establish a mechanistic understanding of reproductive-stage cold tolerance, provide vital selection markers, and identify genetic resources for breeding cold-resilient chickpea cultivars.